EFFECTS OF MULTIPLE INTELLIGENCE-BASED TEACHING ON ENHANCING SCIENCE LITERACY CONCEPTS - Ali Zaman (IJLTP, 2024)
The foremost purpose of this study was to find the effect of multiple intelligence-based teaching on the performance of low achievers in science at middle level. Population of the study was 90 Middle and Secondary Male Schools of District Nowshera, 60 Male students were sample of the study. Study was proceeded using quasi experimental design; involved two groups and it was pre and post tested. One group was called experimental group received an unusual treatment of Multiple intelligence based teaching and other was control group received usual treatment. t-test was used as inferential statistics to compare the means of two groups. It was found that method of multiple intelligence-based teaching when compared, was found better than traditional method. It was recommended that unusual treatment may be implemented in science at middle level to raise the performance of low achievers and teachers may be trained accordingly.